Matrix metalloproteinase 9 promoter activity is induced coincident with invasion during tumor progression. - Kupferman, M; Fini, M; Muller, W; Weber, R; Cheng, Y; Muschel, R (2000)
Matrix metalloproteinase 9 (MMP-9, also known as gelatinase B or 92-kd Type IV collagenase) is overexpressed in many human and murine cancers. We induced carcinomas in mice carrying a transgene that links the MMP-9 promoter to the reporter ss-galactosidase so that activation of the MMP-9 promoter would be indicated by ss-galactosidase. Mammary carcinomas were induced by mating the MMP-9 promoter reporter transgenic mice with mice carrying a transgene for murine mammary tumor virus promoter linked to polyoma middle T antigen, a transgene that leads to rapid development of mammary tumors in female mice. None of the hyperplastic mammary glands and none of the carcinomas in situ expressed ss-galactosidase. However, all invasive tumors had evidence of ss-galactosidase expression. In addition to the breast carcinomas, a malignant teratoma in a female and a papillary adenocarcinoma in the pelvic region of a male arose and were also ss-galactosidase positive. We also induced skin tumors in the mice with the MMP-9 reporter transgene with 7, 12-dimethylbenz[a]anthracene (DMBA) treatment followed by phorbol 12 myristate 13-acetate (TPA). None of the papillomas or in situ carcinomas showed any ss-galactosidase expression, but expression was seen in invasive carcinoma. Although normal skin epithelial cells did not express ss-galactosidase, we did find staining in a few cells at the duct of the sebaceous gland at the base of the hair follicles. The MMP-9 reporter transgene did not lead to expression in the alveolar macrophages, confirming that additional upstream sequences are required for expression in macrophages. These experiments have revealed that MMP-9 promoter activity is induced coincident with invasion during tumor progression. Furthermore, this indicates that the more proximal upstream elements of the promoter are sufficient for MMP-9 transcription during tumor progression.